Zderzenie różnych światów: dzieci z wyjątkowo wysokim potencjałem rozwojowym w relacjach z otoczeniem społecznym = Clash of different worlds: children with exceptionally high developmental potential vs. their social environment - Mróz, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The purpose of this article is to highlight vulnerabilities of highly gifted children in their social environment. Such children`s extraordinary developmental potential is not only a function of their special talents and abilities. American and Canadian researchers emphasize another aspect of developmental potential. This model embraces five forms of overexcitability (psychomotor, sensual, intellectual, imaginational, and emotional) and defines them as dimensions of enhanced mental functioning.
Keywords: dziecko zdolne; środowisko szkolne; wsparcie